Analisis Vegetasi, Karakteristik Habitat dan Pemanfaatan Tumbuhan Herba di Hutan Desa Serdang Kawasan Tahura Kabupaten Karo Sumatera Utara - Julreda Banu Br Sitorus; Melfa Aisyah Hutasuhut; Zahratul Idami (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to analyze the vegetation, habitat characteristics, and utilization of herbaceous plants in the Serdang Village Forest, Tahura Area, North Sumatra Regency. The method used was an exploratory survey with a purposive sampling technique using quadrat plots measuring 5 m × 5 m, arranged in a zigzag pattern with 10 m spacing between plots. The results showed 36 species of herbaceous plants from 17 families. The most frequently found species was Hemigraphis reptans from the Acanthaceae family. The highest importance value index was recorded for Hemigraphis reptans at 44.96, followed by Cyrtandra picta at 27.07 and Pilea melastomoides at 19.59. The diversity index in the Serdang Village Forest was 2.82, categorized as moderate. The habitat characteristics of herbaceous plants in the area include two forest types: primary and secondary. Primary forests have dense canopies and more stable environments, while secondary forests are characterized by more open canopies due to human disturbances such as farming. Herbaceous plants are used as animal feed, fertilizer, traditional medicine, beverages (tea), and livestock bedding.   Keywords: Diversity, Habitat Characteristics, Utilization, Vegetation Analysis